Formulation of Nanostructured Heteroaggregates by Fluidization Technologies. Issue 1 (26th October 2022) - Men, Jialin; Kolan, Subash Reddy; Massomi, Ali; Hoffmann, Torsten; Schmidt, Jochen; Tsotsas, Evangelos; Bück, Andreas
Abstract: Nanostructured heteroaggregates provide improved or new functionalities over homoaggregates due to the formation of heterocontacts. For a high number of heterocontacts, intense mixing of the primary particles and their reaggregation is required. This work presents results using the principle of fluidization for formulation of nanostructured heteroaggregates. Intraaggregate mixing of constituents is evaluated by SEM‐EDX. The feasibility of two technologies, spouted bed and opposed jet fluidized bed, is demonstrated, also showing the variety of structures that can be achieved by the technologies. Abstract : Spouted bed and opposed jet fluidized beds are investigated for their capcability in dry formulation of nanostructured heteroaggregates. Both technologies are feasible, offering a large variety of aggregate sizes and structures. First results for Al2 O3 ‐TiO2 and TiO2 ‐ZrO2 aggregates are presented.